Integrative Analyses of Transcriptomics and Metabolomics in Sex Differentiation of Mulberry Flowers - Liu, Pei-Gang; Xu, Zi-Long; Zhu, Yan; Lin, Tian-Bao; Lv, Zhi-Qiang; Yang, Sheng; Wang, Jin-Wang; Hu, Wen-Jun; Chen, Lin; Wei, Jia (Frontiers in Molecular Biosciences, 2022)
Sex determination and sex differentiation of plants are important physiological processes of plant development. Mulberry (Morus indica L.) is an important economic tree being cultivated in sericulture countries, and mulberry leaf is commonly used for sericulture. The transcriptomic and metabolomic differences between the staminate flowers (SFs) and pistillate flowers (PFs) of mulberry were investigated by RNA sequencing and ultra-performance liquid chromatography-tandem mass spectrometry (UPLC-MS/MS). Overall, we uncovered 4,230 genes and 209 metabolites are significantly differentially expressed between the SFs and PFs of mulberry. The combined transcriptomic and metabolomic analysis revealed these differentially expressed genes (DEGs) and differentially expressed metabolites (DEMs) are involved in flavonoid biosynthesis, galactose metabolism, plant–pathogen interaction, and starch and sucrose metabolism, and these detected DEGs and DEMs may be associated with sex differentiation of mulberry through the regulation of the enrichment pathways, such as the MAPK pathway, flavonoid biosynthesis, galactose metabolism, plant–pathogen interaction, and starch and sucrose metabolism. This study will provide a rich source for the analysis of the molecular mechanism of mulberry sex differentiation processes.